2002
DOI: 10.1177/0018726702055005429
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Savings, Pensions and Life Assurance in 16-21-Year-Olds

Abstract: This article examines the relationship between demographic variables (age, sex, education), knowledge of, and attitudes towards, savings, pensions and life assurance in a sample of British 16-21year-olds.In all 452 young people from a variety of backgrounds completed a questionnaire, divided into three knowledge and three attitude sections. A factor analysis of each of the attitudes towards savings, pensions and life assurance scales revealed clearly interpretable factors. A correlational analysis showed parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 35 publications
1
15
0
2
Order By: Relevance
“…The understanding of banking, pricing and profits follows some years later in early adolescence. Furnham and Goletto-Tankel (2002) found 16-21 year-old British students lamentably ignorant about the topic of pensions and life assurance though they did show attitudes clearly related to technical knowledge about these issues. They concluded that understanding of such issues comes mainly with involvement in the economy.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The understanding of banking, pricing and profits follows some years later in early adolescence. Furnham and Goletto-Tankel (2002) found 16-21 year-old British students lamentably ignorant about the topic of pensions and life assurance though they did show attitudes clearly related to technical knowledge about these issues. They concluded that understanding of such issues comes mainly with involvement in the economy.…”
Section: Discussionmentioning
confidence: 89%
“…Hence, they are unlikely to be good educators of their children. There is also evidence that children express little interest in, and concern with, economic issues that they do not see as currently relevant to them (Furnham & Goletto-Tankel, 2002). However, taxation, perhaps more than pensions and life assurance, is at the heart of many political ideologies and the topic may most beneficially be discussed within that context.…”
Section: Discussionmentioning
confidence: 99%
“…Both the business and economics majors also place less importance than general majors on saving to repay debt. In a sample of British youth (ages 16–21), Furnham and Goletto‐Tankel (2002) found that more education led to more positive attitudes about saving. Our results support the few earlier studies that suggest the specific field of study students pursue, as well as overall level of education, is important.…”
Section: Empirical Specifications—personal Financial Decisionsmentioning
confidence: 98%
“…A study by Furnham and Goletto-Tankel (2002), however, suggested that knowledge of saving, pensions and insurance can be predicted by the attitudes towards these concepts. A study by Furnham and Goletto-Tankel (2002), however, suggested that knowledge of saving, pensions and insurance can be predicted by the attitudes towards these concepts.…”
Section: Attitudesmentioning
confidence: 99%